A meta-analysis of the clinical effectiveness of school scoliosis screening - Fong, Daniel Yee Tak; Lee, Chun Fan; Cheung, Kenneth Man Chee; Cheng, Jack Chun Yiu; Ng, Bobby Kin Wah; Lam, Tsz Ping; Mak, Kwok Hang; Yip, Paul Siu Fai; Luk, Keith Dip Kei (Spine (Philadelphia, Pa. 1976), 2010)
A meta-analysis that systematically reviewed the evaluation studies of a scoliosis screening program reported in the literature. To evaluate the best current evidence on the clinical effectiveness of school screening for adolescent idiopathic scoliosis. The use of school scoliosis screening is controversial, and its clinical effectiveness has been diversely reported. Data sources included 3 databases, namely, PubMed, Google scholar, CINAHL database, and the references from identified reviews and studies. Studies were included if: (1) they adopted a retrospective cohort design; (2) were screened using either the forward bending test (FBT), angle of trunk rotation, or Moiré topography; (3) reported results of screening tests and radiographic assessments; (4) screened adolescents only; (5) reported the incidence of curves with a minimum Cobb angle of 10 degrees or greater; and (6) reported the number of referrals for radiography. Reviews, comments, case studies, and editorials were excluded. Thirty-six studies, including 34 from the 775 initially identified studies and 2 from the references, met the selection criteria. The pooled referral rate for radiography was 5.0%, and the pooled positive predictive values for detecting curves > or =10 degrees , curves > or =20 degrees , and treatment were 28.0%, 5.6%, and 2.6%, respectively. There was substantial heterogeneity across studies. Meta-regression showed that programs using the FBT alone reported a higher referral rate (odds ratio [OR] = 2.91) and lower positive predictive values for curves > or =10 degrees (OR = 0.49) and curves > or =20 degrees (OR = 0.34) than programs using other tests. Only one small study followed students until skeletal maturity and reported the sensitivity of screening; however, the specificity was not reported. No severe publication bias was noted. The use of the FBT alone in school scoliosis screening is insufficient. We need large, retrospective cohort studies with sufficient follow-up to properly assess the clinical effectiveness of school scoliosis screening.